2017
DOI: 10.3390/su9020242
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Interaction of Taxi and Subway Ridership for Sustainable Urbanization

Abstract: A transit ridership study is an essential part of sustainability, and can provide a deep understanding of people's travel patterns for efficient transportation development and urbanization. However, there is a lack of empirical studies comparing subway and taxi services, and their interactions within a city, that is to say, the interdependent transportation networks. Incorporating new data, this study aims to examine the spatial variation of urban taxi ridership due to the impacts of a new subway line operatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 38 publications
0
26
0
Order By: Relevance
“…However, in the peripheral areas of a city where bus service is less robust and the walking distance to the metro station is too long, bicycles and taxis account for higher proportions as the transfer modes [6]. It is also reported that residents who live in suburban areas generate a large number of trips and take taxis to the nearest metro station for maximizing travel efficiency and cost effectiveness [7].…”
Section: Introductionmentioning
confidence: 99%
“…However, in the peripheral areas of a city where bus service is less robust and the walking distance to the metro station is too long, bicycles and taxis account for higher proportions as the transfer modes [6]. It is also reported that residents who live in suburban areas generate a large number of trips and take taxis to the nearest metro station for maximizing travel efficiency and cost effectiveness [7].…”
Section: Introductionmentioning
confidence: 99%
“…Taxis, as a supplement of public transportation, are an important option for individual travel in big cities. Understanding people's movement patterns from their taxi trips can promote sustainable mobility and urban transportation through improving taxi services, taxi sharing, transportation planning, and so on [1][2][3][4][5]. GPS sensors equipped in taxicabs continuously record their locations, and subsequently generate a vast amount of trajectory data.…”
Section: Introductionmentioning
confidence: 99%
“…Taxis provide promptness, door-to-door service, privacy, comfort, high coverage of the city space and all day availability day time, and nowadays are an inevitable part of the communication system of any big city. This is due to the above-mentioned advantages, despite the higher cost of traveling [1][2][3].…”
Section: Introductionmentioning
confidence: 99%